2016
DOI: 10.1021/acs.chemmater.5b03723
|View full text |Cite
|
Sign up to set email alerts
|

A New Set of Isoreticular, Homochiral Metal–Organic Frameworks with ucp Topology

Abstract: A new isoreticular series of metal–organic frameworks, called UHM-25 (UHM: University of Hamburg Materials), based on the copper paddle wheel motif and a novel set of homochiral linkers has been synthesized. Starting from amino acids available from the chiral pool a synthesis procedure was established that allows a straightforward, multigram scale synthesis of homochiral linkers in 4–5 steps. These linkers carry substituents that have been proven useful in stereoselective organic chemistry, such as the Evans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 97 publications
1
18
0
Order By: Relevance
“…In 2000, Kim and co-workers reported the synthesis of chiral MOFs from the enantiopure tartaric-acid-derived bridging ligands, [Zn 3 [44]. Subsequently, the method has been developed, and many research papers have been reported that use naturally occurring enantiopure amino acids and their derivatives [45][46][47][48], tartaric acid derivatives [49,50], and modified 1,1 -binaphthalene-2,2 -diol (BINOL) derivatives [51][52][53] for designing chiral MOFs. Recently, the approach of synthesis has been extended widely with some alteration, which will be described in the review.…”
Section: Chiral Mofs Prepared From Chiral Ligandsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2000, Kim and co-workers reported the synthesis of chiral MOFs from the enantiopure tartaric-acid-derived bridging ligands, [Zn 3 [44]. Subsequently, the method has been developed, and many research papers have been reported that use naturally occurring enantiopure amino acids and their derivatives [45][46][47][48], tartaric acid derivatives [49,50], and modified 1,1 -binaphthalene-2,2 -diol (BINOL) derivatives [51][52][53] for designing chiral MOFs. Recently, the approach of synthesis has been extended widely with some alteration, which will be described in the review.…”
Section: Chiral Mofs Prepared From Chiral Ligandsmentioning
confidence: 99%
“…In 2016, Fröba and associates [47] reported the PSM of the oxazolidinone moieties connected to the MOF UHM-25-Val-Evans (12). The acylation of the MOF (12) was attained by reacting it with propionic anhydride in the presence of a nucleophilic catalyst 4-(dimethylamino)pyridine (DMAP) as shown in Figure 6.…”
Section: Post-synthetic Modification (Psm)mentioning
confidence: 99%
See 3 more Smart Citations